On the application of symbolic interactionism in the study of cultural values (Mongolian Journal of Arts and Culture, 2024)
It is important to closely examine the relationship between symbols and social interactions in the study of cultural values. While semiotics and symbolism theory and methods are widely used in research on Mongolian cultural heritage and values, there is a need for a more detailed examination from the perspective of symbolic interactionism. Applying this theory in cultural studies would provide a clearer explanation by considering social change and structural patterns.From the perspective of symbolic interactionism, studying cultural heritage that represents a specific historical period or space, with its value and significance in nature, society, history, culture, art, and science, involves examining the meaning, symbolism, perceptions, interpretations, memories, and positions of the inheritor of that heritage. It also includes exploring the social causes that influence it. This approach can generally be referred to as a symbolic interactionist perspective.Соёлын үнэт зүйлийн судалгаанд симболик интеракционизмыг хэрэглэх асуудалдХураангуй: Соёлын үнэт зүйлийн судалгаанд бэлгэ тэмдэг, бэлгэдэл, нийгмийн харилцан үйлдлийн хамаарлыг авч үзэх нь чухал ач холбогдолтой. Монголын соёлын өв, үнэт зүйлийн талаарх судалгааны бүтээлүүдэд семиотик, симболизмын арга зүйг нэлээд хэрэглэж буй ч симболик интеракционизмын үүднээс судлах шаардлагатай байна. Энэ баримтлалыг хэрэглэснээр соёлын судалгаанд нийгэм-соёлын өөрчлөлт, нийгмийн бүтцийн хэв маягийг харгалзан илүү тодорхой үр дүнд хүрэхэд дөхөм болох юм. Ялангуяа түүхэн тодорхой үе, орон зайг төлөөлж чадах байгаль, нийгэм, түүх, соёл, урлаг, шинжлэх ухааны үнэ цэн, ач холбогдол бүхий соёлын өвийг судлахад өвлөн уламжлагчийн тухайн өвийн утга, бэлгэдлийн талаарх төсөөлөл, тайлбар, дурсамж, байр суурь, түүнд нөлөөлсөн социаль шалтгааныг илрүүлэхэд ерөнхийдөө симболик интеракционист хандлага чухал юм.Түлхүүр үгс: соёлын өв, судалгааны арга зүй, нийгмийн харилцан үйлдэл, нийгэм-соёл, нийгмийн би, интерпретатив интерактивизм, бэлгэ тэмдэг, метасемиотик